Conducta obstétrica en paciente primigesta de 27 años con 35 semanas, diabetes tipo1, preeclampsia y parto pretérmino’ - Meléndez Pazos, Jennifer Briggitte (2022)
Pregnancy in women with type 1 diabetes mellitus is associated with an increased risk of preeclampsia, congenital malformations, obstetric complications, and neonatal morbidity. These adverse outcomes are related, at least in part, to preconception care, especially the level of glycemic control. Intensive glycemic control and preconception planning have been shown to decrease the rate of stillbirth and malformations seen in pregnant woman complicated by type 1 diabetes mellitus (DMT1). Correct management allows the prevention of maternal and fetal complications that are directly related to this pathology. It is also important that a postpartum follow-up check is carried out, which should be part of the comprehensive evaluation of the pati (publica, 2014)ent with diabetes. Furthermore, recent advances in insulin formulations and delivery methods have increased the number of options available to the obstetric team. In the present clinical case, it was decided to carry out a study om type 1 diabetes mellitus (DMT1) with a 27 year-old primigravid patient with 35.4 weeks of gestations, who presented at the Sagrado Corazón de Jesús hospital. In this way, the risk factors of said patient will be detailed.